Open-source lab how to build your own hardware and reduce research costs - Pearce, Joshua (Elsevier, 2014)
Open-Source Lab: How to Build Your Own Hardware and Reduce Scientific Research Costs details the development of the free and open-source hardware revolution. The combination of open-source 3D printing and microcontrollers running on free software enables scientists, engineers, and lab personnel in every discipline to develop powerful research tools at unprecedented low costs.--Provided by publisher.